PENGARUH PRESTASI MATA PELAJARAN PRODUKTIF DAN PENGALAMAN PRAKTIK INDUSTRI TERHADAP KESIAPAN KERJA SISWA - Mike Elly Anitasari; Slamet Riyadi; Suyitno Suyitno; Menik Darmiati (Jurnal Teknik Otomotif : Kajian Keilmuan dan Pengajaran, 2026)
This study aims to determine the Effect of Productive Subjects and Industrial Practice Experience on the Work Readiness of Class XII TKR SMK YPT Students in the 2024/2025 Academic Year. This type of research is ex post facto with a sample size of 86 students taken using the proportionate stratified random sampling technique. Productive subject achievement data were obtained using the document technique. Industrial practice experience and work readiness data were obtained using the questionnaire method. Data analysis used simple regression analysis and multiple regression analysis. The results of the study showed 1) Productive subject achievement had a significant effect on the work readiness of class XII TKR SMK YPT students in the 2024/2025 academic year with t count = 2.413 (> t table of 1.988) and p = 0.018. 2) Industrial practice experience had a significant effect on the work readiness of class XII TKR SMK students with t count = 2.852 (> t table of 1.988) and p = 0.005. 3) Achievement in productive subjects and industrial internship experience have a significant effect on the work readiness of class XII TKR students with F count = 9.460 (> F table 3.11) and p = 0.000.